Biotic shortcut deselenization coupled to abiotic sulfide oxidation enabled pollutants co-removal and products recovery. (1st October 2021) - Shi, Ling-Dong; Ji, Han-Rui; Jin, Rui; Chen, Yan-Bo; Gao, Tian-Yu; Ma, Fang; Zhao, He-Ping
Highlights: Shortcut deselenization saved roughly one half of operation time and carbon source. Sulfide and selenite were co-removed abiotically at optimum pH of 10 and S/Se of 4. The coupled process enabled >95% removal of both selenate and sulfide stably. High-purity hexagonal selenium (97.4%) was formed for recover and reuse favorably. Abstract: Selenate and sulfide are both contaminants which severely pollute water bodies. Respective bioremediation of selenate- and sulfide-contaminated wastewaters requires abundant electron donors and acceptors. Here, we present a novel concept coupling biological selenate to selenite (shortcut deselenization) and chemical sulfide-driven selenite reduction, to remove multiple pollutants simultaneously. Vial tests showed that shortcut deselenization could save at least two thirds of operation time and one third of carbon source, compared to the complete deselenization to elemental selenium. Subsequent co-removal of sulfide and selenite was optimized at reaction pH of ∼10 and reactant molar ratio of ∼4. Using a newly-designed continuous flow system, >95% removal of both selenate and sulfide was achieved by coupling shortcut deselenization to sulfide oxidation. A series of characterization tools revealed that the final collected precipitates were comprised of high-purity hexagonal selenium (97.4%, wt) and inconsiderable sulfur (2.6%, wt). Superior over selenate-reducing solutions generally producing selenium mixed with reagents or microorganisms, the selenium products generated here were highly purified thus very favorable for further recovery and reuse. Overall, this proof-of-concept study provided a promising technology not only for co-removal of multiple pollutants, but also for substantial costs saving, as well as for valuable products recovery. Graphical abstract: Image, graphical abstract